Remembering enslavement : reassembling the Southern plantation museum - Potter, Amy E.; Hanna, Stephen P.; Alderman, Derek H.; Carter, Perry; Bright, Candace Forbes; Butler, David L. (David Lawrence) (The University of Georgia Press, 2022)
"Remembering Enslavement explores plantation museums as sites for contesting and reforming public interpretations of slavery in the American South. Emerging out of a three-year National Science Foundation grant (2014-17), the book turns a critical eye toward the growing inclusion of the formerly enslaved within these museums, specifically examining advances but also continuing inequalities in how they narrate and memorialize the formerly enslaved. Using assemblage theory as a framework, Remembering Enslavement offers an innovative approach for studying heritage sites, retelling and remapping the ways that slavery and the enslaved are included in southern plantation museums. It examines multiple plantation sites across geographic areas, considering the experiences of a diversity of actors: tourists, museum managers/owners, and tour guides/interpreters. This approach allows for an understanding of regional variations among plantation museums, narratives, and performances, as well as more in-depth study of the plantation tour experience and public interpretations. The authors conclude the book with a set of questions designed to help professionals reassemble plantation museum narratives and landscapes to more justly position the formerly enslaved at their center."--Page [4] of cover.
Keywords: Historical museums -- Southern States.; Slavery -- Southern States -- Historiography.; Plantation life -- Southern States -- Historiography.; Historic sites -- Southern States.; Histoire -- Musées -- États-Unis (Sud); Vie dans les plantations -- États-Unis (Sud) -- Historiographie.; Lieux historiques -- États-Unis (Sud); Historic sites; Historical museums; Plantation life -- Historiography; Slavery -- Historiography; Southern States; Electronic books.